The Relationship Between Social Media Use and Athlete Mental Health: A Literature Review - Gurning, Nico Febrian; Simbolon, Rifaldo Patriot; Rizqiansyah, Ridho; Sembiring, Revaldo; Elmahdi, Ody Pratama (Jurnal Inovasi Olahraga, 2025)
Purpose of the study: This systematic literature review examines the relationship between social media use and mental health outcomes among competitive athletes across various sports disciplines. The study aims to synthesize existing research to understand how social media platforms impact athlete psychological well-being, performance anxiety, and overall mental health. Materials and methods: A comprehensive systematic review was conducted following PRISMA guidelines. Electronic databases including PubMed, PsycINFO, SPORTDiscus, and Web of Science were searched from January 2015 to December 2024. Search terms included combinations of "social media," "athletes," "mental health," "depression," "anxiety," and "psychological well-being." Inclusion criteria encompassed peer-reviewed studies examining competitive athletes aged 16-35 years with validated mental health assessments. Results: The systematic search yielded 847 initial articles, with 32 studies meeting inclusion criteria after screening and quality assessment. Studies included 8,471 athletes across individual and team sports. Results indicate a complex relationship between social media use and athlete mental health, with both positive and negative associations identified. Excessive social media use (>3 hours daily) was associated with increased rates of depression (OR: 1.67, 95% CI: 1.23-2.27) and anxiety (OR: 1.52, 95% CI: 1.18-1.95). However, moderate, purposeful social media use showed potential benefits for social support and career development. Conclusions: Social media presents both opportunities and risks for athlete mental health. The relationship is dose-dependent and context-specific, with excessive use correlating with negative mental health outcomes while moderate, strategic use may provide benefits. Sports organizations should develop comprehensive social media literacy programs and mental health support systems.